2003
DOI: 10.7748/ns.17.44.53.s57
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative wound infections

Abstract: Continuous education of all healthcare professionals in basic infection control procedures, policies and new information on antimicrobial resistance is recommended to increase detection and identification of surgical wound infections. A follow-up study should be conducted to measure the improvement in the use of aseptic techniques by both nurses and physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…11,12 Postoperative wound infection increases the length of stay in hospital was also observed by other authors like Michalopoulos A et al and Perl TM. 11,13 Present findings were comparable to those of Umesh SK et al who found that the mean duration of postoperative stay in patients with SSI was 9 days. 14 The present study shows that 20 (20.83%) of thyroidectomy cases had post-operative wound infection followed by laparoscopic appendicectomy (17.77%), fistulectomy and other surgeries like fibro adenoma excision (16.66% each), but the difference distribution of proportion of these cases as per type of operation was not significant (p>0.05).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11,12 Postoperative wound infection increases the length of stay in hospital was also observed by other authors like Michalopoulos A et al and Perl TM. 11,13 Present findings were comparable to those of Umesh SK et al who found that the mean duration of postoperative stay in patients with SSI was 9 days. 14 The present study shows that 20 (20.83%) of thyroidectomy cases had post-operative wound infection followed by laparoscopic appendicectomy (17.77%), fistulectomy and other surgeries like fibro adenoma excision (16.66% each), but the difference distribution of proportion of these cases as per type of operation was not significant (p>0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations were made by some authors where more probability of post-operative wound infection in cases where duration of operation was more. 13 An interesting observation was that the infection rate was significantly low when the patients were operated as the first case on a particular table. It was 8.57% for the patients who were operated as the first case; it was 9.03% for the second case, 9.52% for the third case and 14.78% for more than third case.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this aim, there is evidence that the practitioners experience problems when performing aseptic procedures (Ward, 2000;Michalopoulos and Sparos, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…open, fresh, accidental wounds),and (i.e. old traumatic wounds with retained devitalized tissue and those that involve existing clinical infection or perforated viscera) (16) The possible mode of transmission for hospital acquired infection are either cross-infection due to indirect spread of the pathogens via patients contact stay or autoinfection from an endogenous flora found in the patient. For example surgical site infection can be caused by an endogenous flora that translocations to a normally sterile site or when the sterile peritoneal cavity is contaminated by spillage from the gastrointestinal tract; and by an exogenous source of microbial contamination that comes from the surgical team, surgical instrument and the theatre environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The type of surgical procedure and duration of the operation also contribute to the occurrence of the infection. Further-more, aseptic procedures were not followed strictly by the majority of the nurses and physicians in several practice areas and is found to be significant for the transmission of the infection (16) All patients undergoing a surgical procedure are placed at some risk of infections. These risk factors are: the number and virulence of the contaminating micro -organisms ,the operative and environmental factors like the surgeon` skill and cleanness of the theatre , the nature of the operation like its classification such as clean, clean--9 -contaminated, and contaminated , Patients' age, smoking, obesity, malnutrition and immunosuppressant therapy , Local factors such as presence of wound drains, hair removal or previous irradiation of site (17).…”
Section: Literature Reviewmentioning
confidence: 99%